Graduates of New University Careers: Unequal Competition on the Labour Market - Damian Simón, Javier (2017)
The purpose of the study is to describe the process of job insertion in a context of the local labour market of the graduates to identify traits of discrimination originated by their hybrid professional profile . A case study and a qualitative approach were used to investigate the graduates of the first two generations of the Business Sciences Degree of a small Mexican public university. The results contradict the advantages attributed to hybrid university careers, far from facilitating the incorporation to the work, it found that hybrid graduates compete of unequal way for job offers due to two situations: lack of social knowledge of their profession by all employers that originates the absence of demand of these professionals, and lack of professional identity of graduates that causes they are unable to justify and defend the usefulness of their hybrid training.